2022
DOI: 10.1038/s41467-022-35582-x
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater depletion in California’s Central Valley accelerates during megadrought

Abstract: Groundwater provides nearly half of irrigation water supply, and it enables resilience during drought, but in many regions of the world, it remains poorly, if at all managed. In heavily agricultural regions like California’s Central Valley, where groundwater management is being slowly implemented over a 27-year period that began in 2015, groundwater provides two–thirds or more of irrigation water during drought, which has led to falling water tables, drying wells, subsiding land, and its long-term disappearanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 61 publications
0
36
0
1
Order By: Relevance
“…Specifically, Argus et al (2022) concluded that the southern SJV lost 1.5 ± 0.4 km 3 yr –1 during 2006–2021 . Similarly, Liu et al (2022) observed a decrease in groundwater storage (2.55 ± 0.60 km 3 yr –1 ) in the southern SJV over the present drought (2019–2022) . Depleted aquifers will be more sensitive to As and Se contaminant fluxes, and during droughts, any As/Se contamination imparted by produced water disposal will unlikely be diluted by mixing with meteoric or surface waters.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Argus et al (2022) concluded that the southern SJV lost 1.5 ± 0.4 km 3 yr –1 during 2006–2021 . Similarly, Liu et al (2022) observed a decrease in groundwater storage (2.55 ± 0.60 km 3 yr –1 ) in the southern SJV over the present drought (2019–2022) . Depleted aquifers will be more sensitive to As and Se contaminant fluxes, and during droughts, any As/Se contamination imparted by produced water disposal will unlikely be diluted by mixing with meteoric or surface waters.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the outcome of "dry wells and reduced rural water security" through the groundwater-connected systems framing. For this example, we use the setting of California's Central Valley and use a narrative approach to weave together multiple perspectives, data sources, and formats In California's Central Valley, groundwater pumping accelerates during times of drought (Liu et al 2022), further depleting groundwater resources. As this occurs, wells across the state run dry (Jasechko and Perrone 2020).…”
Section: Invigorating Groundwater Sustainability With Sustainability ...mentioning
confidence: 99%
“…During droughts, farmers and communities heavily rely on pumping groundwater to sustain agricultural operations and meet domestic water needs. Geological surveys report a dramatic decline in groundwater levels over the past 3 decades as levels are only temporarily recharged during short rainfalls but are followed by longer periods of groundwater loss during times of drought [37 ▪ ]. Media reports and the California Department of Water Resources confirm increasing rates of communities receiving drought funding for water supply challenges and reliance on bottled water in the Central Valley [38–41].…”
Section: California's Central Valleymentioning
confidence: 99%